Pervasive Heavy Alcohol Use and Correlates of Increasing Levels of Binge Drinking among Men Who Have Sex with Men, San Francisco, 2011. - Santos, Glenn-Milo; Jin, Harry; Raymond, H. (Journal of Urban Health, 2015)
Heavy episodic drinking, 'binge drinking', is highly prevalent among men who have sex with men (MSM) and is associated with sexual risk behaviors and HIV seroconversion in this population. We characterized the magnitude of binge drinking and explored correlates of increasing levels of binge drinking among MSM in San Francisco. In this study, 67 % of MSM reported binge drinking in the prior year. The mean number of drinking days in the past month was 11.6. On average, we estimate that 2,699,372 drinks are consumed by MSM in San Francisco every month. Increasing levels of binge drinking was independently associated with younger age, modest income, being born in the United States, never accessing alcohol treatment and reporting unprotected insertive anal intercourse. Our findings underscore the need to target effective strategies to address heavy alcohol consumption and highlight the urgent need to develop novel interventions beyond traditional alcohol treatment settings among MSM.